Hypomagnesiemia and diabetes melitus type 2 - Jandrić-Kočić, Marijana C; Todorovic, Nevena; Knezevic, Snezana (Medicinski časopis, 2023)
Hypomagnesemia is a relatively common and often unrecognized electrolyte disorder in type 2 diabetes mellitus. This review presents the pathophysiology of magnesium deficiency in type 2 diabetes mellitus, its role in the development of disease complications, and the effect of magnesium supplementation. The literature search was conducted using the following keywords: magnesium, diabetes mellitus, complications, supplementation, within PubMed, Emabase, Scopus, SCIndex and Hrčak for the period from 2001 to 2023. Type 2 diabetes mellitus causes increased excretion of magnesium in the urine. On the other hand, reduced concentrations of magnesium in the blood of people with type 2 diabetes mellitus predispose to complications of the disease. A significant number of randomized, controlled studies and meta-analyses indicate the beneficial effect of magnesium supplementation in the control of hyperglycemia, dyslipidemia, and hypertension in people with type 2 diabetes mellitus. Routine monitoring and correction of magnesium concentrations in the blood of people with type 2 diabetes mellitus can help control and delay complications. diseases. Further research is needed to establish firm guidelines for clinical practice.
Keywords: magnesium, diabetes mellitus, complications, supplementation